Neutropenic enterocolitis and colonic perforation in a patient with breast carcinoma treated with taxane-based chemotherapy: a case report and review of the literature - Demirel, Aslıhan; Kihtir, Selçuk; Geceer, Gürkan; Koçulu, Safiye; Çevik, Esin (The European Research Journal, 2018)
Neutropenic enterocolitis or typhlitis is one of the rare but high mortality acute complications of neutropenia that develops in immunosuppressed patients due to chemotherapy. It is a segmental cecal and ascending colon inflammation that can progress to necrosis and perforation. Although it is mostly observed in myelosupressed and immunosuppressed patients, like those who have leukemia and lymphoma, it can also be observed in malignancies treated with myelosupressive chemotherapy. It has been reported particularly in patients with solid tumors treated with taxane-based chemotherapy. In this article, a 40-year-old patient with invasive ductal breast carcinoma is presented, who was diagnosed with neutropenic enterocolitis and colonic perforation that developed 6 days after chemotherapy (Docetaxel 75 mg/m2 and cyclophosphamide 600 mg/m2). If neutropenic fever, abdominal pain, abdominal distension, and tenderness develops in a patient under taxane-based chemotherapy, neutropenic enterocolitis is a condition that must definitely be considered. It should be noted that it is possible to reduce mortality and morbidity by means of appropriate antibiotics and a timely surgical intervention.